"It's Like Going Back in Time": How White Retirees Use Expatriation to Reclaim White Dominance. (August 2019) - Goss, Devon R.
The number of Americans and Canadians choosing to live outside of their home countries after retirement is increasing rapidly, with Mexico as the primary destination for emigration. The majority of these expatriates are white. This study explores how race affects the experiences of emigration and expatriation for these retirees. In-depth interviews with 30 white expatriate retirees living in Mazatlán, Mexico, reveal that white expatriates respond to a growing sense of racial victimization and nostalgia by framing their emigration as a chance to reclaim their superior and racialized social standing. Specifically, white expatriates use three strategies to explain how race affected their experiences in Mexico: escaping, wherein they come to Mexico to avoid the racial diversification of their home countries; evoking, in which they position Mexico as a place to recoup old-fashioned values; and reclaiming, wherein Mexico is perceived as a chance to regain their whiteness as standing.